2017
DOI: 10.1016/j.ijpharm.2017.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Targeting energy metabolism of cancer cells: Combined administration of NCL-240 and 2-DG

Abstract: Cancer cells increase their metabolism to produce the energy and biomolecules necessary for growth and proliferation. Thus, energy metabolism pathways may serve as targets for anti-cancer therapy. NCL-240 is a second generation anti-cancer drug belonging to the PITenins class of PI3K-Akt inhibitors. Our analysis suggested that NCL-240 caused disruptions in mitochondrial oxidative phosphorylation and up-regulated glycolysis, as evidenced by the loss of NMR peaks for the amino acid products derived from the TCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…39 In this study, we demonstrate that the synergy between PD The glucose analogue, 2-DG, which is phosphorylated by hexokinase, competes with 6-phosphate glucose (6-P-G) to inhibit glycolysis, resulting in cancer cell death due to cell energy ATP deprivation. 41,42 The activation of AKT is commonly observed in a variety of cancers and seems to be intricately associated with aerobic glycolysis, proliferation and invasiveness. 40 In this study, we found that 2-DG and PD both inhibited cell viability in 4T1 and MCF-7 ( Figure 1) and that PD combined with 2-DG obviously induced apoptosis and led to a reduction in cell proliferation and migration in 4T1 and MCF-7 compared to the individual treatment groups ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In this study, we demonstrate that the synergy between PD The glucose analogue, 2-DG, which is phosphorylated by hexokinase, competes with 6-phosphate glucose (6-P-G) to inhibit glycolysis, resulting in cancer cell death due to cell energy ATP deprivation. 41,42 The activation of AKT is commonly observed in a variety of cancers and seems to be intricately associated with aerobic glycolysis, proliferation and invasiveness. 40 In this study, we found that 2-DG and PD both inhibited cell viability in 4T1 and MCF-7 ( Figure 1) and that PD combined with 2-DG obviously induced apoptosis and led to a reduction in cell proliferation and migration in 4T1 and MCF-7 compared to the individual treatment groups ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that 2-DG induces the phosphorylation of AKT and the efficacy of clinical trials has previously been limited by the systemic toxicity. 41,42 The activation of AKT is commonly observed in a variety of cancers and seems to be intricately associated with aerobic glycolysis, proliferation and invasiveness. 43,44 In this study, we found that the mechanism of action of the treatment combination is that PD blocks the activation of the PI3K/ AKT pathway by 2-DG ( Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Similar and higher concentrations of 2DG improved the responses in vitro of a range of breast cancer cell lines to mitochondria targeted drugs [20,21], a glucopyranoside [22], and inhibitors of BCL family members [23]. Analogous in vitro data have been reported for cervical cancer [24], melanoma [25], glioblastoma [26], and osteosarcoma [27]. In the only study targeting a clear cell pathology, 5 mM 2DG reduced proliferation and viability of primary cultures of renal clear cell carcinoma cells [18].…”
Section: Introductionmentioning
confidence: 59%
“…Of note, these elevated 2DG concentrations employed in vitro are well above the maximum plasma levels (C max ) achieved in cancer patients in two published dose-finding clinical trials. In a study of patients with advanced solid malignancies, the maximum tolerated dose for 2DG, administered daily during the first two weeks of a three week cycle, was 45 mg/kg, resulting in a C max 0.449 mM [28], which is 10-fold lower than concentrations typically employed in in vitro studies [18][19][20][21][22][23][24][25][26][27]. In a combination trial with docetaxel for a range of advanced solid tumors, the clinically tolerable dose for 2DG, administered daily during the first and third weeks of a four week cycle during the dose-escalation phase, was 63 mg/kg/day, resulting in a C max of 0.707 mM [29].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most studies focus on an inhibitor named 2-DG which can be phosphorylated by hexokinase. The use of 2-DG can help adriamycin and paclitaxel to elevate reacting in human osteosarcoma-bearing mice and of small cell lung cancer [22]. In fact, complete break of glycolysis will lead to severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%